Role of the lateral prefrontal cortex in speech monitoring - Riès, Stephanie K.; Xie, Kira; Haaland, Kathleen Y.; Dronkers, Nina F.; Knight, Robert T. (Frontiers in Human Neuroscience, 2013)
The role of lateral prefrontal cortex in speech monitoring has not been delineated. Recent work suggests that medial frontal cortex (MFC) is involved in overt speech monitoring initiated before auditory feedback. This mechanism is reflected in an event-related potential (ERP), the error negativity (Ne), peaking within 100 ms after vocal-onset. Critically, in healthy individuals the Ne is sensitive to the accuracy of the response; it is larger for error than correct trials. By contrast, patients with lateral prefrontal cortex (lPFC) damage are impaired in nonverbal monitoring tasks showing no amplitude difference between the Ne measured in correct vs. error trials. Interactions between the lPFC and the MFC are assumed to play a necessary role for normal action monitoring. We investigated whether the lPFC was involved in speech monitoring to the same extent as in non-linguistic actions by comparing performance and EEG activity in patients with lPFC damage and in aged-matched controls performing linguistic (Picture Naming) and non-linguistic (Simon) tasks. Controls did not produce enough errors to allow the comparison of the Ne or other ERP in error vs. correct trials. PFC patients had worse performance than controls in both tasks, but their Ne was larger for error than correct trials only in Naming. This task-dependent pattern can be explained by lPFC-dependent working-memory requirements present in non-linguistic tasks used to study action monitoring but absent in picture naming. This suggests that lPFC may not be necessary for speech monitoring as assessed by simple picture naming. In addition, bilateral temporal cortex activity starting before and peaking around vocal-onset was observed in lPFC and control groups in both tasks but was larger for error than correct trials only in Naming, suggesting the temporal cortex is associated with on-line monitoring of speech specifically when access to lexical representations is necessary.